Implementation of SAK E-MKM: Key Factor in Improving MSME Performance - Setiawan, Aris; Sari, Wilda; Afif, Ali; Yahya, Rizki Fakhrul; Mayasafitri, Rina (Jurnal Akuntansi, 2024)
Abstract Purpose - This study aims to test and analyze the factors that influence the application of SAK-EMKM. The factors used are the perceptions of MSME actors, SAK-EMKM socialization, SAK-EMKM training and human resource (HR) competencies. Design/methodology/approach - This research uses quantitative methods, and the data obtained comes from distributing questionnaires to MSME actors in Pontianak City. Data in this research was processed with the assistance of software IMB SPSS 25.Findings - The results showed the results of the Adjusted R Square value of 0.883, this means that the application of SAK-EMKM can be explained by MSME perceptions, SAK-EMKM socialization, SAK-EMKM training and Human Resource Competencies (HR) by 88.3%. In the influence test, it is known that MSME perceptions, SAK-EMKM socialization and HR competencies have a positive and significant effect on the application of SAK-EMKM in MSME actors, while SAK-EMKM training has no effect on the application of SAK-EMKM. This study recommends that MSME actors be able to record financial statements in accordance with SAK-EMKM. Research limitations/implications – This research has limitations on the scope of the research area. Keywords: Implementation of SAK-EMKM, MSME Actors, and MSME Perception